STRUKTUR SOSIAL MASYARAKAT NELAYAN KOTA BENGKULU : Kajian Struktural Tentang Kemiskinan Nelayan Kota Be~gkulu (Social Structure of Fisherman Community at Bengkulu City)1 - Apriyanty, Henny; S. Alikodra, Hadi; M, Kooswardono; Sutarto, Endriatmo; Kolopaking, Lala M (Jurnal AGRISEP, 2006)
Fisherman community in Bengkulu city which divided into groups based on ethnic and authority of production  asset. Sumberjaya  district is the modern area fishery, the profit sharing system indicates the large imbalance  relatively  in distribution  which  cause  distribution  not  covered  all  out relatively  in eaming distribution. And in Teluk Sepang district which is fishery area, the profit sharing system indicates small imbalance relatively, even still cause distribution which not covered all out. The tightly relationship client patron  has seen clearly  in Sumberjaya district  which make  high dependance  relatively  between owner of production equipment with laborer of ship fisherm8n, hence pONerty will keep existing, while in Teluk  Sepang  district  has not  seen the patron  client  relationship,  however  the pONerty  still  existing because of the limited production tool. Marketing distribution of fish based on kind of fisherman exertion. FIsherman exertion which using ·purseine", "gill ner,  and "trammel net"  chain of marketing to 'consumer is long precisely.    This matter  is because  of the commodity  which  resulted  is the export  commodity, because  of the commodffy  wich resulted is the  export,  while  kind of fisherman  exertion  which  using·waiing·,  fishing  rod  and"mono  filament", the marketing  chain  is short relatively  because  of the local commodity.  However,  the  existing  long  chain  marketing  cause  narrow  margin  which  received  by fisherman.